Characteristic analysis and forecast of electricity supply and demand in APEC - Yong Sun; Li Zhu; Zhaofeng Xu; Lingjuan Xiao; Jianyun Zhang; Jiqiang Zhang (Global Energy Interconnection, 2019)
The Asia Pacific Economic Cooperation (APEC) comprises of the world’s largest producers and consumers of energy, accounting for 60.3% of primary energy supply, 50.0% of final energy consumption, and 63.0% of electricity generation worldwide in 2016. This study discusses the primary energy supply and final energy consumption situation of the APEC and analyzes the characteristics of electricity in terms of its generation structure based on fuel, consumption by the end-use sector, access to electricity, and so on. The renewable energy and electricity generation projections up to 2030 based on trends in the APEC are also assessed. It is seen that electricity in final energy consumption has been on an upward trend, with an average annual growth rate of about 4.8% during 2006-2016; in 2016, its share reached 24.3%. The industry sector consumes the largest share of electricity, accounting for about 45.5% in 2016. Coal supply and consumption peaked in 2011 and then began to decline, while renewable energy has been on an upward trend, with its primary energy supply share increasing from 4.80% in 2010 to 6.29% in 2016. Solar photovoltaic and onshore wind power are on the verge of costing less than the operating cost of existing coal-fired plants in 2018. In the APEC’s target scenario in which renewable energy is doubled, the predicted net growth from 2017 to 2030 of solar, wind, and hydro power is about 963, 497, and 157 GW, respectively, and to reach this target, the APEC economies need to accelerate renewable energy development. Keywords: APEC, Electricity supply and demand, Characteristics analysis, Renewable energy